The Analysis of Collocations Use the Film Entitled “Rambo: Last Blood” By Adrian Grunberg - Rosanna Marpaung; Musawer Hakimi; Jontra Jusat Pangaribuan (Merwin Publisher, 2024)
Collocation is defined as a combination of words in a language, which occurs very often and more often than happens by chance. The aims of this study were to find out What are the types of collocations that used in the film entitled